Targeted Droplet‐Digital PCR as a Tool for Novel Deletion Discovery at the DFNB1 Locus. Issue 1 (29th October 2015) - Tayoun, Ahmad N. Abou; Mason‐Suares, Heather; Frisella, Ashley L.; Bowser, Mark; Duffy, Elizabeth; Mahanta, Lisa; Funke, Birgit; Rehm, Heidi L.; Amr, Sami S.
Abstract : Unlike traditional PCR, targeted droplet‐digital PCR is a robust, highly sensitive technology capable of detecting all reported, and potentially novel, DFNB1 copy number changes using a few probes. Here, we describe such an assay and the identification of a novel deletion at the DFNB1 locus. ABSTRACT: Pathogenic variants at the DFNB1 locus encompassing the GJB2 and GJB6 genes account for 50% of autosomal‐recessive, congenital nonsyndromic hearing loss in the United States. Most cases are caused by sequence variants within the GJB2 gene, but a significant number of DFNB1 patients carry a large deletion ( GJB6 ‐D13S1830) in trans with a GJB2 variant. This deletion lies upstream of GJB2 and was shown to reduce GJB2 expression by disrupting unidentified regulatory elements. First‐tier genetic testing for hearing loss includes GJB2 sequence and GJB6 ‐D13S1830 deletion analysis; however, several other deletions in this locus, each with distinct breakpoints, have been reported in DFNB1 patients and are missed by current panels. Here, we report the development of a targeted droplet digital polymerase chain reaction‐based assay for comprehensive copy‐number analysis at the DFNB1 locus that detects all deletions reported to date. This assay increased detection rates in a multiethnic cohort of 87 hearing loss patients with only one identified pathogenic GJB2 variant. We identify two deletions, one of which is novel, in two patients (2/87 or 2.3%), suggesting that other pathogenic deletions at the DFNB1 locus may be missed. Mapping the assayed DFNB1 deletions also revealed a ∼95 kb critical region, which may harbor the GJB2 regulatory element(s).